Project Based Learning Model to Improve Early Childhood Social Skills in Ternate - Radjiman Ismail; Tatang Subagyo (PT Mattawang Mediatama Solution, 2023)
This study aims to improve social skills through the project based learning (PjBL) learning model. The research method uses action research developed by Lewin. Data collection techniques using observation sheets in the form of a Likert scale 1-3. Data analysis techniques using the mix method developed by Crewell. The research population was group B early childhood students in the city of Ternate. The research subjects were 25 early childhood students from two early childhood education schools. From an early age, children need to be introduced to and develop social skills in everyday life. This skill is important so that children are able to interact with peers or more adults. Good social skills can help children develop their potential to the fullest. The ability of social skills is shown through the ability to communicate, respect each other, take responsibility for each other, and empathize with each other. The results of the research at the end of the second cycle using the t test, obtained data t-count> t-table. These results can be concluded that the project based learning learning model has an influence on the ability of social skills. It is recommended that early childhood teachers can use project-based learning models to improve children's social skills. Keywords: social skills, project based learning model.